Identifikasi Karakteristik Desa/Kelurahan Di Provinsi Nusa Tenggara Timur Menggunakan Analisis Gerombol - Andrew Donda Munthe (Jurnal Statistika Terapan (ISSN 2807-6214), 2023)
Grouping of villages by clustering analysis can result in the identification to the appropriate policy programs to each cluster formed. The clustering algorithm that can be used on mixed variables of village grouping is the Gower Method (Gower’s distance). The purpose of this study is to apply the Gower Method to village clustering in Nusa Tenggara Timur Province based on 13 mixed variables. The data used in this study was sourced from Village Potential Data Collection (PODES) in 2021. The results showed that the optimal cluster that formed from the application of the Gower Method was 3 clusters. The first cluster consisted of 1.063 villages, the second cluster consisted of 870 villages and the third cluster consisted of 1.517 villages. Based on the visualization of the results of the cluster, the area with the highest tendency to development achievement is the village in the third cluster, while the lowest is in the villages of the first cluster members.